The impact of regional and functional integration on the post-entry performance of knowledge intensive business service firms - Andreas Koch; Harald Strotmann (European Regional Science Association (ERSA), 2004)
Knowledge intensive business service firms (KIBS) are an important element of modern economies and thus attracting increasing interest in scientific research. In the existing literature it is argued that due to the important role of knowledge, innovation and user-producer interaction in the KIBS sector, functional and regional integration are particularly decisive for the firms' post-entry development. Nevertheless, few existing studies are dealing with questions of entrepreneurship in the KIBS sector using micro firm data. This contribution gives an empirical analysis of the determinants of post-entry performance of KIBS in three German metropolitan regions. Due to the lack of suitable firm micro data, telephone interviews with 547 firm founders have been conducted. By applying multivariate estimation methods it can be shown that functional linkages to knowledge providers, customers and co-operation partners indeed matter for the performance of young KIBS. Regarding regional integration, however, especially a high diversification of spatial reach is proved to be crucial. JEL-Classification: D21, J23, L80, O30 Keywords: Employment growth; Entrepreneurship; Entry; Innovation; Knowledge-intensive business services; Post-entry performance
Keywords: D21; J23; L80; O30; 330; Employment growth; Entrepreneurship; Entry; Innovation; Knowledge-intensive business services; Post-entry performance